Pressure-Controlled Ventilation-Volume Guaranteed Mode Combined with an Open-Lung Approach Improves Lung Mechanics, Oxygenation Parameters, and the Inflammatory Response during One-Lung Ventilation: A Randomized Controlled Trial. (29th April 2020) - Li, Jianli; Cai, Baogui; Yu, Dongdong; Liu, Meinv; Wu, Xiaoqian; Rong, Junfang
Abstract : We evaluated the effectiveness of pressure-controlled ventilation-volume guaranteed (PCV-VG) mode combined with open-lung approach (OLA) in patients during one-lung ventilation (OLV). First, 176 patients undergoing thoracoscopic surgery were allocated randomly to four groups: PCV+OLA (45 cases, PCV-VG mode plus OLA involving application of individualized positive end-expiratory pressure (PEEP) after a recruitment maneuver), PCV (44 cases, PCV-VG mode plus standard lung-protective ventilation with fixed PEEP of 5 cmH2 O), VCV+OLA (45 cases, volume-controlled ventilation (VCV) plus OLA), and VCV (42 cases, VCV plus standard lung-protective ventilation). Mean airway pressure (P mean ), dynamic compliance (Cdyn), PaO2 /FiO2 ratio, intrapulmonary shunt ratio (Qs/Qt), dead space fraction (V D / V T ), and plasma concentration of neutrophil elastase were obtained to assess the effects of four lung-protective ventilation strategies. At 45 min after OLV, the median (interquartile range (IQR)) P mean was higher in the PCV+OLA group (13.00 (12.00, 13.00) cmH2 O) and the VCV+OLA group (12.00 (12.00, 14.00) cmH2 O) than in the PCV group (11.00 (10.00, 12.00) cmH2 O) and the VCV group (11.00 (10.00, 12.00) cmH2 O) (P < 0.05 ); the median (IQR) Cdyn was higher in the PCV+OLA group (27.00 (24.00, 32.00) mL/cmH2 O) and the VCV+OLA group (27.00 (22.00, 30.00) mL/cmH2 O) than in the PCV group (23.00 (21.00, 25.00) mL/cmH2 O) and the VCV group (20.00 (18.75, 21.00) mL/cmH2 O) (P < 0.05 ); the median (IQR) Qs/Qt in the PCV+OLA group (0.17 (0.16, 0.19)) was significantly lower than that in the PCV group (0.19 (0.18, 0.20)) and the VCV group (0.19 (0.17, 0.20)) (P < 0.05 ); V D / V T was lower in the PCV+OLA group (0.18 ± 0.05 ) and the VCV+OLA group (0.19 ± 0.07 ) than in the PCV group (0.21 ± 0.07 ) and the VCV group (0.22 ± 0.06 ) (P < 0.05 ). The concentration of neutrophil elastase was lower in the PCV+OLA group than in the PCV, VCV+OLA, and VCV groups at total-lung ventilation 10 min after OLV (162.47 ± 25.71, 198.58 ± 41.99, 200.84 ± 22.17, and 286.95 ± 21.10 ng / mL, resp.) (P < 0.05 ). In conclusion, PCV-VG mode combined with an OLA strategy leads to favorable effects upon lung mechanics, oxygenation parameters, and the inflammatory response during OLV.